Revisiting the Electricity Consumption-Economic Growth Nexus in Angola: The Role of Exports, Imports and Urbanization - Solarin, Sakiru Adebola; Shahbaz, Muhammad; Shahzad, Syed Jawad Hussain (International Journal of Energy Economics and Policy, 2016)
The present study aims to reinvestigate the relationship between electricity consumption and economic growth in Angola by introducing exports, imports and urbanization in the production function. We utilize the combined cointegration method to test the long-run relationship for the period of 1971-2012. Whilst accommodating structural breaks, the ARDL bounds test approach is applied to examine the robustness of the long-run relationship in the variables. The results reveal that electricity consumption boosts economic growth but urbanization impairs it. The VECM causality results unveil the feedback relationship of electricity consumption with economic growth, exports and imports. It is, therefore, suggested that the policy makers should formulate the policies to improve the electricity supply that in turn will enhance the economic growth. Keywords: Electricity consumption, economic growth, combined cointegration test, Granger causality test JEL Classifications: C32; O55, Q43